The neurobiology of aggression and violence - Rosell, Daniel R.; Siever, Larry J. (CNS spectrums, 2015)
Aggression and violence represent a significant public health concern and a clinical challenge for the mental healthcare provider. A great deal has been revealed regarding the neurobiology of violence and aggression, and an integration of this body of knowledge will ultimately serve to advance clinical diagnostics and therapeutic interventions. We will review here the latest findings regarding the neurobiology of aggression and violence. First, we will introduce the construct of aggression, with a focus on issues related to its heterogeneity, as well as the importance of refining the aggression phenotype in order to reduce pathophysiologic variability. Next we will examine the neuroanatomy of aggression and violence, focusing on regional volumes, functional studies, and interregional connectivity. Significant emphasis will be on the amygdala, as well as amygdala–frontal circuitry. Then we will turn our attention to the neurochemistry and molecular genetics of aggression and violence, examining the extensive findings on the serotonergic system, as well as the growing literature on the dopaminergic and vasopressinergic systems. We will also address the contribution of steroid hormones, namely, cortisol and testosterone. Finally, we will summarize these findings with a focus on reconciling inconsistencies and potential clinical implications; and, then we will suggest areas of focus for future directions in the field.